AI-Based Diagnostic Shell - Verma, R. L.; Oulaganathan, S.; Vidhya R., S. Maya (Defence Science Journal, 2013)
This paper datails the design and implementation of an AI-based diagnostic shell. The shell has a user-interface which takes in the complaint and aids the user throughout the consultation. The 'expert knowledge' is acquired and encoded in the form of 'IF-THEN' rules, The control mechanism routes through the rules chaining first backwards to identify a fault and then forwards to confirm it.Explanation facilities have been provided to enable the user query the reason for any question asked, a facility to go back and re-answer any previous question, and a trace and explanation of the path of reasoning. This shell was developed and first used for the diagnosis of a digital exchange. It was then applied for the fault-finding of the moving target indicator used in the radar.